"BUT WE'RE TALKING ABOUT HALF-BEAST HUMAN": CONVERSATIONAL IMPLICATURE IN A TELEVISION TALK SHOW WITH ANWAR IBRAHIM - Anisa Larassati (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2016)
This study examines how a Malaysian opposition leader, Anwar Ibrahim, flouted the Grice's (1975) maxims during the interview in Kick Andy show. The talk show was aired in 2007 when Indonesia and Malaysia were on political dispute caused by the abusive behaviour of some Malaysians towards Indonesian domestic migrant workers. The results illustrate that the interviewee did not simply answer the questions as commonly expected, but rather flouted frequently. Several strategies of flouting the maxims such as giving overstatements, understatements, hints, and figure of speech were used. Throughout the show, it appeared that Anwar wanted the audience to believe that Malaysian government allegation (corruption and sodomy) towards him was groundless. He also showed his support for Indonesian workers and raised the issue without being asked. In this case, Anwar flouted the maxims not only to raise implicature but also to serve his particular goals as a politician, i.e. to establish a positive image.Keywords: implicature, maxims, opposition, politician, talk-show